Pembiayaan Murabahah, Musyarakah, Qardh Dan NPF Terhadap Profitabilitas BUS Tahun 2018-2022 - Shinta Nuriyah, Neng Liana; Setyaningsih, Nina Dwi (Jurnal E-Bis, 2024)
Sharia commercial banks are financial institutions that carry out their activities by following sharia principles and also play a role in managing payment flows. As an integral part of the sharia financial sector, sharia commercial banks have an important role in driving Indonesia's economic growth. This research aims to investigate the impact of murabahah, musyarakah, qardh, and non-performing financing (NPF) on the profitability of sharia commercial banks from 2018 to 2022. The research population consists of sharia commercial banks registered with the Financial Services Authority (OJK), with a total sample of five sharia commercial banks, selected through a purposive sampling method. The research approach used is descriptive quantitative with data analysis using multiple linear regression. The results of the analysis show that partially, murabahah and NPF financing have a significant influence on profitability, while musyarakah and qardh financing do not have a significant influence. Overall, murabahah, musyarakah, qardh and NPF financing together influence the profitability of sharia commercial banks.